Synthesis and Characterization of Calcium Oxide Nanoparticles from Duck Eggshells using Ball Milling Methods - Ade Yeti Nuryantini; Citra Deliana Dewi Sundari; Halimahtussa’diah Halimahtussa’diah; Bebeh Wahid Nuryadin (Jurnal Kimia Valensi, 2019)
Calcium oxide (CaO) nanoparticles have been successfully synthesized from duck eggshells using ball milling method followed by simple calcination at 700°C for 7 hours. The observation on the morphology, size and shape of the particles of the eggshells powder was conducted through scanning electron microscope (SEM). The milling time was varied, i.e. 2, 6, 10, and 20 hours to observe the difference on the size of the produced particle. SEM images shows that the smallest average particle diameter was 520 nm, achieved by 20 hours of milling. When the particles were calcined, the average diameter was further reduced to 394 nm. The X-ray diffraction (XRD) analysis shows that the resulting particles contain calcium oxide, calcium hydroxide, and calcium carbonate.